Silence of a scream: application of the Silences Framework to provision of nurse-led interventions for ex-offenders. (May 2015) - Eshareturi, Cyril; Serrant, Laura; Galbraith, Victoria; Glynn, Martin
The Silences Framework and its underpinning concept of 'Screaming Silences' was originally presented with the invitation for further peer review and utilisation in other contexts in order to test its usefulness and enable critique by a wider audience. This paper reports the use of the framework in a study researching nurse-led interventions for released ex-offenders. Screaming Silences were situated in how an issue, as experienced by ex-offenders, screams out to them in relation to their health and its impact on their reality while remaining silent in the consciousness of society and the application of practice. In addressing these Screaming Silences, we associated the Silences Framework within marginal discourses as they are less prioritised by policy and frequently positioned as far removed from what society considers as normal. Screaming Silences were situated in the subjective experiences of ex-offenders known as the 'listener' and the social and personal context in which these experiences occurred. We affirmed that the framework is ideally suited for researching issues which are under-researched, silent from policy discourse and excluded from practice, as it is oriented towards exploring individual experiences by valuing individual interpretations of events.